2023
DOI: 10.1371/journal.pone.0292900
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, attitudes, and practices of dietary supplements among middle-aged and older adults in Asir region, Saudi Arabia: A cross-sectional study

Amani Alhazmi,
Beena Briget Kuriakose,
Sakeena Mushfiq
et al.

Abstract: The objectives of this study were to 1) identify the prevalence of dietary supplements (DS) among middle-aged and older adults; 2) determine attitudes toward DS and patterns of DS usage among middle-aged and older adults; and 3) assess the association of sociodemographic, clinical, and lifestyle factors with DS attitudes and DS usage. A cross-sectional online survey was undertaken among middle-aged and older adults. Data were collected by an online self-administered pretested questionnaire used as a study tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…8 More recent data from a cross-sectional survey of 501 individuals aged over 45 residing in Saudi Arabia in 2021 showed that the prevalence of dietary supplement use was 50.7% and was lower in those under 60 (54.9%) compared to older people (59.9%). 9 Statistical data on the consumption of dietary supplements indicate a growing interest in products that improve health and slow the aging process, which is promoted by media marketing. 10 Some plant-based anti-aging dietary supplements may protect against age-associated health problems, such as sarcopenia and metabolic syndrome, perhaps by affecting hormone concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…8 More recent data from a cross-sectional survey of 501 individuals aged over 45 residing in Saudi Arabia in 2021 showed that the prevalence of dietary supplement use was 50.7% and was lower in those under 60 (54.9%) compared to older people (59.9%). 9 Statistical data on the consumption of dietary supplements indicate a growing interest in products that improve health and slow the aging process, which is promoted by media marketing. 10 Some plant-based anti-aging dietary supplements may protect against age-associated health problems, such as sarcopenia and metabolic syndrome, perhaps by affecting hormone concentrations.…”
Section: Introductionmentioning
confidence: 99%